The legal system for negotiating in the electronic contract - alqudah, Yassin Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to discover the importance of the legal system for negotiation in the electronic contract. Through what was offered for electronic negotiation, the following results and recommendations were reached: The period of negotiations prior to the contract is no less important than the period after the contract. Because it is a period of preparation for the contract, and whenever the preparation was good, the contract was good and achieved the interest of the contractors and included the conditions that prevent the disputes between them. The study recommended to: we hope the Jordanian legislator to provide a legal organization for the negotiation stage with focus on the principle of goodwill. The negotiating parties should take this into account when negotiating so that they have a legal basis for those who violate the obligations imposed by the principle of goodwill when negotiating. Therefore, we propose to the Jordanian legislator a third clause to the text of Article 202 of the Jordanian Civil Law to be as follows: The parties to the contractual negotiation must abide by the obligations imposed by the principle of good faith.